Effect of Hubbard U on the construction of low-energy Hamiltonians for LaMnO(3) via maximally localized Wannier functions - EDERER, CLAUDE; KOVACIK, ROMAN (American Physical Society, 2011)
We use maximally localized Wannier functions to construct tight-binding (TB) parametrizations for the e(g) bands of LaMnO(3) based on first-principles electronic structure calculations. We compare two different ways to represent the relevant bands around the Fermi level: (i) a d-p model that includes atomic-like orbitals corresponding to both Mn(d) and O(p) states in the TB basis, and (ii) an effective e(g) model that includes only two e(g)-like Wannier functions per Mn site. We first establish the effect of the Jahn-Teller distortion within the d-p model, and then compare the TB representations for both models obtained from GGA+U calculations with different values of the Hubbard parameter U. We find that in the case of the d-p model the TB parameters are rather independent of the specific value of U, if compared with the mean-field approximation of an appropriate multiband Hubbard Hamiltonian. In contrast, the U dependence of the TB parameters for the effective e(g) model cannot easily be related to a corresponding mean-field Hubbard model, and therefore these parameters depend critically on the specific value of U, and more generally on the specific exchange-correlation functional, used in the electronic structure calculation.
PUBLISHED
Keywords: Condensed matter physics; ELECTRONIC-STRUCTURE; MAGNETIC-STRUCTURES; HARTREE-FOCK